Information security analysis on physical security in university x using maturity model - Khairunnisak Nur Isnaini; Siti Alvi Solikhatin (Universitas Ahmad Dahlan, 2020)
The threat of physical security can be from human factors, natural disasters, and information technology itself. Therefore, to prevent threats, we need the right tools to control current activities, evaluate potential impacts, and make appropriate plans so that business processes at X University will not be affected. This research starts by analyzing the problems that arise, followed by collecting the data needed, discussing the results, and making conclusions and recommendations that can be given. The method uses quantitative descriptive research. The research instrument uses interviews and questionnaire techniques. COBIT 5 is used as a framework for measuring the performance that is being implemented and will be achieved. Maturity models are used to measure current and future activities. The goal to be achieved is that the organization can create a physical security environment by the CIA principle (confidentiality, integrity, & availability). Positioning results are at level 3, meaning that the process is currently running in two main standard operating procedures. However, this evaluation specifically on the DSS5.5.5 subdomain (Providing Service Support-Managing physical security for IT Assets) in COBIT 5, and the results are still below the level 3 standard (Established Process), at 2.9 points. So, the right suggestion is to keep activities safe, one of which is to improve facilities and infrastructure, one of which is the use of biometric control in data center management rooms or other rooms with limited access.